2013
DOI: 10.1002/cncr.28410
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with K‐RAS wild‐type colorectal cancer

Abstract: BACKGROUND The CO.20 trial randomized patients with K‐RAS wild‐type, chemotherapy‐refractory, metastatic colorectal cancer to receive cetuximab (CET) plus brivanib alaninate (BRIV) or CET plus placebo (CET/placebo). METHODS Quality of life (QoL) was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 at baseline and at 2, 4, 6, 8, 12, 16, and 24 weeks until disease progression. Predefined coprimary QoL endpoints were time to deterioration (first worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Cancers harbor significant genetic heterogeneity [37], and patterns of relapse following many therapies are due to evolved resistance to treatment. While efforts have been made to combine targeted therapies, a lack of success, rising drug costs and significant levels of toxicity have stymied efforts to effectively treat cancer with multi-drug combinations using currently approved therapeutics [38]. Consequently, this approach aims to target many disease-specific pathways simultaneously - using low-cost chemistry with little to no toxicity - to address this heterogeneity (in contrast to the limited number of actionable targets that have become the norm in combination chemotherapy).…”
Section: Introductionmentioning
confidence: 99%
“…Cancers harbor significant genetic heterogeneity [37], and patterns of relapse following many therapies are due to evolved resistance to treatment. While efforts have been made to combine targeted therapies, a lack of success, rising drug costs and significant levels of toxicity have stymied efforts to effectively treat cancer with multi-drug combinations using currently approved therapeutics [38]. Consequently, this approach aims to target many disease-specific pathways simultaneously - using low-cost chemistry with little to no toxicity - to address this heterogeneity (in contrast to the limited number of actionable targets that have become the norm in combination chemotherapy).…”
Section: Introductionmentioning
confidence: 99%
“…Combining brivanib with cetuximab increased toxicity compared to cetuximab alone, with the overall incidence of Pgrade 3 AEs at 78% vs. 53% (p < .001), respectively [33]. HRQL analysis showed a shorter time to quality of life deterioration among patients treated with brivanib alaninate plus cetuximab compared to control, potentially due to increased rates of fatigue and gastrointestinal AEs [34].…”
Section: Multikinase-inhibitors In Later Lines Of Treatmentmentioning
confidence: 97%
“…In fact, the combination of the two drugs led to an accelerated deterioration of HRQoL compared with single-agent cetuximab. The researchers suggested that this could be a result of the increased toxicity of the combined therapy, with the side effects offsetting any potential HRQoL benefit of delayed disease progression [32]. …”
Section: Clinical Evidence Of Pros and Hrqol In Mcrcmentioning
confidence: 99%